PENDIDIKAN BUDAYA MULTIKULTURAL SEKOLAH NEGERI - Wilhelmus, Ola Rongan (Lembaga Penelitian STKIP Widya Yuwana, 2025)
Public schools are basically owned by the Indonesian people and nation. The schools open for accepting any teachers, students, educational staff and employees from various tribes, ethnicities, religions, groups and social classes in Indonesia to study and work at the schools. Public schools can thus be said to be multicultural schools. The context of globalization and the socio-cultural diversity of the Indonesian nation have made multicultural education in the public schools a necessity. It is because multicultural education can create a comfortable school environment contributing to the development of the school environment that is safe, communicative, inclusive, tolerant, participatory and respect to the sosi-cultural diversity. The paper was written through a library research process. The processs was carried out systematically by collecting, reading, processing, and concluding information and scientific research data obtained from various written reading materials related to multicultural education in the public schools. The paper was written with the aim of exploring theoretical and practical concepts regarding multicultural education in the public schools. The paper is expected to have a significant contribute to the development of theoretical concepts on multicultural education, as well as practical input for school leaders and members for further development of multicultural education, particularly in the public schools.